2016
DOI: 10.1053/j.jvca.2015.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Left Atrial Opacity

Abstract: REFERENCE 1. Pencina M, D'Agostino RB, D'Agostino RB Jr, et al: Evaluating the added predictive ability of a new marker: From area under the ROC curve to reclassification and beyond. Stat Med 27:157-172, 2008 http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Various pathophysiologic theories have been proposed including spontaneous inversion, negative suction through the intracardiac vents during de-airing manouevres, 6 , 7 external compression from lung hyperinflation, and iatrogenic inadvertent inclusion of the LAA while closing the superior end of VSDs. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Various pathophysiologic theories have been proposed including spontaneous inversion, negative suction through the intracardiac vents during de-airing manouevres, 6 , 7 external compression from lung hyperinflation, and iatrogenic inadvertent inclusion of the LAA while closing the superior end of VSDs. 8 …”
Section: Discussionmentioning
confidence: 99%
“…The authors previously reported an invagination of left atrial appendage probably due to a left atrial vent that was inserted through a patent foramen ovale during the repair of a child with Tetralogy of Fallot. 1 With this in mind, as well as the finding that the newly encountered left atrial opacity had the same echo density as the surrounding cardiac tissues, a careful examination of the appendage with minimal disturbance to the hemodynamic parameters was done. This revealed an inversion of the left atrial appendage and it was immediately restored to its normal configuration.…”
Section: Diagnosis: Left Atrial Appendage Inversionmentioning
confidence: 99%